1986
DOI: 10.1111/j.1600-0447.1986.tb06244.x
|View full text |Cite
|
Sign up to set email alerts
|

REM latency and core temperature relationships in primary depression

Abstract: REM latency and rectal and ear canal temperature were studied simultaneously in 11 controls and nine depressed patients; seven of the patients were studied when recovered. REM latency was shorter in the depressed group compared with controls and lengthened with recovery. The nocturnal and ear canal temperatures were higher in the depressed group compared with controls and decreased with recovery. REM latency and the nocturnal rectal temperature were negatively correlated when all the nights of the depressed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…The temperature minimum increased (consistent with the decrease in amplitude) in the luteal phase compared to the follicular menstrual cycle phase. Most likely, this increase is a function of progesterone in the luteal phase and is consistent with reports of higher temperatures (mostly nocturnal but some daily) in depression and LLPDD (Avery et al, 1982(Avery et al, ,1986Pflug et al, 1976Pflug et al, ,1981Severino et al, 1991;Wehr et al, 1980). The increased mesor of the temperature rhythm in the luteal phase compared to that in the follicular phase is consistent with the report by Lee (1988) and with changes both in amplitude and minimum levels, reflecting a change in the overall waveform.…”
Section: Amplitude Changessupporting
confidence: 90%
See 2 more Smart Citations
“…The temperature minimum increased (consistent with the decrease in amplitude) in the luteal phase compared to the follicular menstrual cycle phase. Most likely, this increase is a function of progesterone in the luteal phase and is consistent with reports of higher temperatures (mostly nocturnal but some daily) in depression and LLPDD (Avery et al, 1982(Avery et al, ,1986Pflug et al, 1976Pflug et al, ,1981Severino et al, 1991;Wehr et al, 1980). The increased mesor of the temperature rhythm in the luteal phase compared to that in the follicular phase is consistent with the report by Lee (1988) and with changes both in amplitude and minimum levels, reflecting a change in the overall waveform.…”
Section: Amplitude Changessupporting
confidence: 90%
“…Thus symptomatic conditions (the LL phase) and groups (PMDD) are associated with an increase in the temperature mesor. Treatment effects are associated with a decrease in the temperature mesor, consistent with some reports in the literature in which decreased temperature values or metabolic rates were associated with remission of symptoms (Avery et al, 1982(Avery et al, , 1986Pflug et al, 1976Pflug et al, ,1981Souetre et al, 1989;Wu et al,1992).…”
Section: Amplitude Changessupporting
confidence: 89%
See 1 more Smart Citation
“…An analysis of the rhythm from previous circadian studies, however, does not appear to well fit this pattern [23], and also goes against observations of 24-hour elevations of temperature found in other studies [27]. These observations of in-Rausch/Johnson/Corley/Hobby/ Shendarkar/Fei/Ganapathy/Leibach creased daytime temperatures combine with observations of increased nocturnal temperatures in depressed patients [22,[28][29][30], suggesting an overall elevation of body temperature. Nonetheless, this study does not preclude an expectation of phase advance in a portion of the depressed population consistent with the literature.…”
Section: Discussionmentioning
confidence: 64%
“…Most [16][17][18][19][20][21][22][23], but not all [24,25], of these studies showed disturbed circadian temperature rhythms in patients with depression and other mood disorders [26,27]. Some [22,[28][29][30], but not all [31], studies on depressed patients have documented high nocturnal temperatures and higher mean 24-hour temperatures [28]. Another study of bipolar depressed patients [27] indicated higher mean daily temperatures from continual measurements.…”
Section: Introductionmentioning
confidence: 99%